2022
DOI: 10.3389/fmicb.2022.992823
|View full text |Cite
|
Sign up to set email alerts
|

The application of enzymatic fermented soybean effectively regulates associated microbial communities in tea soil and positively affects lipid metabolites in tea new shoots

Abstract: Compared with traditional organic fertilizer, fermented soybean is a better fertilizer resource in tea plantations. The application of organic fertilizer is a feasible practice to mitigate the soil degradation caused by the overuse of chemical fertilizers, which can effectively regulate soil microbial communities in tea plantations. However, the effects of fermented soybean on soil microbial communities, soil metabolites and metabolites in tea new shoots have not been systematically demonstrated, and their int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 60 publications
2
6
0
Order By: Relevance
“…In the study, the relative abundance of Actinobacteria in soils under compost mixed chemical fertilizer treatments was significantly lower than that of in soils under unfertilized and chemical fertilizer alone (p < 0.05), indicating that the application of compost created a relatively nutrient environment. The results were consistent with the former studies that investigated other organic fertilizer applications [12,25,31,39]. The abundance of Actinobacteria was inversely correlated with AK (Figure 4a) and TN (Figure 4b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the study, the relative abundance of Actinobacteria in soils under compost mixed chemical fertilizer treatments was significantly lower than that of in soils under unfertilized and chemical fertilizer alone (p < 0.05), indicating that the application of compost created a relatively nutrient environment. The results were consistent with the former studies that investigated other organic fertilizer applications [12,25,31,39]. The abundance of Actinobacteria was inversely correlated with AK (Figure 4a) and TN (Figure 4b).…”
Section: Discussionsupporting
confidence: 92%
“…However, long-term excessive application of chemical fertilizer causes soil acidification, resulting in a nutrient imbalance in tea gardens, which is not conducive to sustainable development. Fertilization management has been widely applied in tea plantation management [12,[30][31][32]. Combining the use of biofertilizers is thought to be a successful method of fertilization for maintaining agricultural growth that is sustainable [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…This is beneficial for improving the yield and quality of tea. Previous studies in our laboratory have shown that fermented soybeans as fertilizers can improve soil nutrient status, regulate related microbial communities, and positively affect the budding of tea [10]. This study laid the foundation for our further application of enzymatically fermented organic materials in tea plantations.…”
Section: Introductionmentioning
confidence: 67%
“…Ning et al found that soil organic matter, soil catalase activity, and urease activity increased significantly after applying organic in vegetable fields [44]. Zhang et al found that the activities of soil sucrase, soil acid phosphatase, and soil urease were significantly higher than those of inorganic fertilizer after applying soybean fertilizer in the tea garden [10]. In this study, it was found that after the application of enzymatic rapeseed cake, the content of soil organic matter (OM), total nitrogen (TN), total phosphorus (TP), available nitrogen (AN), and available phosphorus (AP) was significantly higher than that of the control with no fertilization and urea treatment, and slightly higher than that of the naturally fermented rapeseed cake treatment.…”
Section: The Enzymes and Microorganisms Jointly Promoted The Transfor...mentioning
confidence: 99%
“…Our results were consistent with that reported by Chen et al (2019) [78], who also documented the decline of relative abundance of Pseudomonas and Streptomyces. The drop in relative abundance of Pseudomonas may be related to soil P level, since the Pseudomonas is the major P-solubilizing bacteria in croplands [79], and dominant in soils with low P level [80], the higher P content as a result of amendment of organic supplement may depress its growth. However, Hu et al (2018) [22] reported that integrated application of only higher amount of organic manure or crop straw and synthetic fertilizers increased the relative abundance of Pseudomonas against NPK while the incorporation of lower doses of organic materials showed no effect in a calcareous Karst soil (pH 7.28).…”
Section: Phod-harboring Bacteriamentioning
confidence: 99%